Spatial overlap in powerline collisions and vehicle strikes obscures the primary cause of avian mortality - Marc S. Travers; Scott Driskill; Caitlin Scott; Karim Hanna; Skyler R. Flaska; Molly Bache; André F. Raine (Journal for Nature Conservation, 2023)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Seabird mortality induced by land‐based artificial lights - Airam Rodríguez; Nick D. Holmes; Peter G. Ryan; Kerry‐Jayne Wilson; Lucie Faulquier; Yovana Murillo; André F. Raine; Jay F. Penniman; Verónica Neves; Beneharo Rodríguez; Juan J. Negro; André Chiaradia; et al. (Conservation Biology, 2017)
Artificial lights at night cause high mortality of seabirds, one of the most endangered groups of birds globally. Fledglings of burrow‐nesting seabirds, and to a lesser extent adults, are attracted to and then grounded (i.e., forced to land) by lights when they fly at night. We reviewed the current state of knowledge of seabird attraction to light to identify information gaps and propose measures to address the problem. Although species in families such as Alcidae and Anatidae can be grounded by artificial light, the most affected seabirds are petrels and shearwaters (Procellariiformes). At least 56 species of Procellariiformes, more than one‐third of them (24) threatened, are subject to grounding by lights. Seabirds grounded by lights have been found worldwide, mainly on oceanic islands but also at some continental locations. Petrel breeding grounds confined to formerly uninhabited islands are particularly at risk from light pollution due to tourism and urban sprawl. Where it is impractical to ban external lights, rescue programs of grounded birds offer the most immediate and employed mitigation to reduce the rate of light‐induced mortality and save thousands of birds every year. These programs also provide useful information for seabird management. However, these data are typically fragmentary, biased, and uncertain and can lead to inaccurate impact estimates and poor understanding of the phenomenon of seabird attraction to lights. We believe the most urgently needed actions to mitigate and understand light‐induced mortality of seabirds are estimation of mortality and effects on populations; determination of threshold light levels and safe distances from light sources; documentation of the fate of rescued birds; improvement of rescue campaigns, particularly in terms of increasing recovery rates and level of care; and research on seabird‐friendly lights to reduce attraction.

Food use is affected by the experience of nest predation: implications for indirect predator effects on clutch size - Liana Y. Zanette; Keith A. Hobson; Michael Clinchy; Marc Travers; Tony D. Williams (Oecologia, 2013)

Indirect predator effects on clutch size and the cost of egg production - Marc Travers; Michael Clinchy; Liana Zanette; Rudy Boonstra; Tony D. Williams (Ecology Letters, 2010)
Ecology Letters (2010) 13: 980–988 Abstract Predator‐induced changes in physiology and behaviour may negatively affect a prey’s birth rate. Evidence of such indirect predator effects on prey demography remains scarce in birds and mammals despite invertebrate and aquatic studies that suggest ignoring such effects risks profoundly underestimating the total impact of predators. We report the first experimental demonstration of indirect predator effects on the annual ‘birth’ rate resulting from negative effects on the size of subsequent clutches laid by birds. We manipulated the probability of nest predation and measured the size of subsequent clutches and multiple indices of the mother’s physiological condition, while controlling for food availability, date and stage of breeding. Females subject to frequent experimental nest predation laid smaller subsequent clutches and were in poorer physiological condition, particularly regarding non‐resource‐based indices (e.g. oxidative stress and glucocorticoid mobilization) consistent with both a response to the threat of predation and an increased cost of egg production.

Influence of freshwater and terrigenous material on nutrients, bacteria and phytoplankton in a high island lagoon: Mayotte, Comoro Archipelago, Indian Ocean - Eveline Vacelet; André Arnoux; Bernard A. Thomassin; Marc Travers (Hydrobiologia, 1998)